Розширене фізичне моделювання фотоелектричних панелей для підвищення їх тривалої продуктивності - Шутєєв, Н. В.; Галат, О. Б. (ХНУРЕ, 2025)
The global transition toward sustainable energy sources places photovoltaic (PV) technology at the forefront of the world’s future power infrastructure. While the solar industry has matured significantly, a critical challenge remains: the often-observed gap between the predicted energy performance of a solar panel and its actual output over its 25–30 year lifespan. This performance discrepancy is driven by the complex interplay of material degradation, environmental stressors (such as temperature and varying light irradiance), and the inherent limitations of conventional models. The primary aim of this work is to address this reliability gap by developing a sophisticated physical and numerical model of solar cell. This model is designed to accurately predict energy yield, simulate internal degradation mechanisms, and integrate strategies for enhancing panel sensitivity and signal stability under real-world operating conditions.
Keywords: фотоперетворювач; photovoltaic (PV) technology